b =-3 a=2 c= 4 (1)-b square + a + c
WritersParadise01:
is in the question, it is -b²+a+c or b²+a+c ?
Answers
Answered by
0
Hi mate here is your ans Hope it's helpful for you :)
Attachments:
![](https://hi-static.z-dn.net/files/d32/93e349f3aaaed291f07a2e348a90f8ef.jpg)
Answered by
0
hey dear sweet friend here is your answer
=> (-b)²+a+c
put the value
=> -(-3)²+2+4
=> -(9)+2+4
=> -9+2+4
=> -9+6
=> -3 is your answer
=> (-b)²+a+c
put the value
=> -(-3)²+2+4
=> -(9)+2+4
=> -9+2+4
=> -9+6
=> -3 is your answer
Similar questions